Idiopathic granulomatous mastitis: diagnostic dilemma - K., Akhila; V., Ravikumar; P., Panchami (International Surgery Journal, 2022)
We report a case of Idiopathic granulomatous mastitis in a 21 years old female who came to our hospital with complaints of painful lump in her left breast because the results of initial excision of fibroadenoma, when re-exploration was done to rule out any foreign body – excision biopsy was done. However, the final histopathological diagnosis was granulomatous mastitis with suture granuloma, no evidence of malignancy. A review of literature revealed that idiopathic granulomatous mastitis has a tendency to affect young women. Clinical diagnosis and imaging has often been difficult. Complete resection or corticosteroid therapy can be recommended as appropriate treatment. Since recurrence rate is as high as 50%, long term follow up is indicated in such patients.